Assessing the chest radiographic severity of pulmonary tuberculosis among hiv and nonhiv patients - Santhi Varatharaja, Pillai (2008)
Pulmonary tuberculosis (PTB) is the most common infectious disease in developing countries and the development of complications remains a difficult diagnostic challenge. The proportion of tuberculosis developing in the immunocompromised hosts is especially high and is one of the leading causes of morbidity and mortality. The main purpose of this study was to determine the association between the chest radiograph severity of pulmonary tuberculosis with HIV status (non-HIV and HIV). This study also evaluated the differences in the various chest radiograph appearances of pulmonary tuberculosis among the above mentioned two study groups. This was a retrospective study, focused on adult pulmonary tuberculosis patients with non-HIV and HIV coinfection form Hospital Raja Perempuan Zainab-11, Kota Bharu. Those patients who had clinical symptoms and signs of PTB with either sputum smear AFB or culture MTB proven pulmonary tuberculosis were recruited for this study Mean age of the patients in both non-HIV and HIV groups were 46.5 and 32.6 respectively. Ninety three percent (93%) of non-HIV and 94% of HIV patients demonstrated abnormal chest radiograph during pre-treatment phase. Whereas the chest radiograph done six months after the commencement of treatment demonstrated 18% and 31% of normal finding in non-HIV and HIV patients, respectively. There was no significant statistical difference found among these two study groups in the chest radiograph severity/extent of PTB during pre-treatment (p-value=0.668) and posttreatment (p-value=O.l35) phases. Comparison of the two groups showed HIV patients with PTB had higher incidence of pleural effusion (23% vs. 14%, p-value=0.081) and miliary tuberculosis (7% vs. 3%, p-value=0.196), even-though non-significant. Nevertheless, hilar/mediastinal lymphadenopathy (32% vs. 4%, p-value<0.001) demonstrated significant difference in the HIV group. Whereas in non-HIV patients more of pleural thickening (36% vs. 11%, p-value<0.001), bronchiectasis (16% vs. 5%, p-value=0.007) and lung fibrosis (41% vs. 17%, p-value<0.001) were demonstrated. Lesser incidence of chest radiograph presentation with cavitation (33% vs. 24%, pvalue= 0.177) found in the HIV group, however no significant statistical difference among the two study groups. There was no significant statistical difference found among the two study groups in the chest radiograph severity of PTB during pre-treatment (p-value=0.668) and (pvalue= O.l35) post-treatment phases. This study also demonstrated significant statistical difference among the PTB with HIV co-infected patients by showing more number of normal chest radiograph in the post-treatment phase. HIV with PTB coinfected patient had considerable differences in the various chest radiograph presentations specifically with hilar/mediastinal lymphadenopathy. While pleural thickening, bronchiectasis, fibrosis and consolidation found more commonly in non-HIV patients.